DEVELOPMENT OF MEDICINAL VEGETABLE CULTIVATION FOR FAMILY USE (TOSGA) IN REALIZING SUSTAINABLE AGRICULTURAL INNOVATION FOR WOMEN IN PENGABUAN VILLAGE, ABAB DISTRICT, PALI REGENCY, SOUTH SUMATRA - Masona, Sarion; Nasution, Adam S.; Putra, Erwin Hendra (Transpublika Publisher, 2024)
In Pengabuan Village, women dominate poverty. The vulnerability of this group is explained by the fact that they do not have enough training, experience, and a source of investment to put food on their table (to meet even basic family needs, including healthcare). This journal in this case study is the implementation of the Independent Agriculture for Empowerment Village Women (